Inequalities in Food Consumption the Colombian Households : Results from the National Survey of Nutritional Status (2021)
ABSTRACT: Introduction: adverse socioeconomic conditions may cause food intake characterized by inequality that derives in malnutrition increases. Objective. To identify inequalities in food consumption among the Colombian population according to socioeconomic status and the food security classification for households. Methods. the data were obtained from the 2005 National Survey of Nutritional Status, and the analysis used the first 24-hour recall n=39,413 Colombians. The statistical analysis took into account descriptive statistics and 95% confidence intervals. A multivariate analysis was performed through multinomial logistic regression models, with each of the food groups as a dependent variable. Finally, a latent class analysis was performed to understand the heterogeneity of the inequalities in food consumption in the households. Results. Low-socioeconomic status households showed higher consumption of cereals, tubers and plantains, non-alcoholic beverages, and fats. I contrast, higher socioeconomic status households showed higher consumption of dairy products, fruit, vegetables, and sugars/sweets. The food security classification found that food-secure households had a higher consumption of meat, dairy, vegetables, fruit, and sugars/sweets. Households classified as food-insecure showed a higher consumption of cereals, tubers and plantains, and non-alcoholic beverages. The consumption of tubers and plantains showed a clear social gradient, in higher socioeconomic status there was lower consumption probability of those products. Conclusion. There are inequalities in food consumption in Colombia according to socioeconomic status and the food security classification; therefore, people and families with the most unfavorable socioeconomic status have diets with les nutritional value.